Bandwidth Enhancement Of Pyramidal Horn Antenna Using Dielectric Resonator Feeder - Othman, Ali (2013)
Nowadays, satellite communications play an important role in telecommunications. As a result, high gain and broadband antennas are part of the solution to establish a concept of wide frequency usage. Pyramidal horn antenna is most widely used as feed in satellite communication and tracking due to suitability for high gain and broadband applications. Generally, pyramidal horn antennas are fed by a coaxial feed transition. However, there is a fundamental limitation on the operating bandwidth (BW) of the coaxial feed transition and is often being considered as narrowband device. This thesis describes the development and analysis of the BW enhancement feeding technique for pyramidal horn antenna using a dielectric resonator (DR) feeder. The hybrid dielectric resonator antenna (DRA) found to be in essence contributing the BW of the design feeder. The combinational effect of two radiators produces multiple resonant frequencies and provides wideband 48.15% of measured -10 dB return loss impedance BW centered at 14.23 GHz, while that of the pyramidal horn with conventional coaxial feed transition is 13.27%. The designed feeder provide an average simulated gain of 16.22 dBi with flexibility in the impedance BW and the far-field radiation characteristics appears to be satisfied within the operating BW. The pyramidal horn improved the gain of the hybrid DRA by 12.34 dBi. The effectiveness of proposed design and preliminary results of the design have shown a potential to exploit the designed feeder to be used in a parabolic antenna for tracking of satellites applications at 10 to 18 GHz. In conclusion this work offers a new, efficient and relatively simple alternative feeding technique configuration for pyramidal horn antenna.